ChemInform Abstract: One‐Dimensional Gold Clusters in HP‐Ce7Au13+xGe10‐x. Issue 43 (7th October 2013) - Heymann, Gunter; Heying, Birgit; Riecken, Jan F.; Huppertz, Hubert; Poettgen, Rainer
Abstract Single crystals of the high‐pressure phase of Ce7Au13+xGe10‐x are obtained by treatment of CeAuGe at 9.5 GPa and 1473—1523 K in a multi‐anvil press.